Pengaruh Fasilitas Donor Darah Terhadap Minat Donor di UDD PMI Kota Surakarta Bulan Maret Tahun 2021 - Vivi Nurul Laily; Ni'mah Hidayatul Laili (Indonesian Journal on Medical Science, 2022)
Preservation of voluntary blood donors is very important to maintain the availability of blood stock in the blood donation unit with various efforts made to produce safe blood. To determine the effect of blood donation facilities on donor interest in the BDU of the Indonesian Red Cross Surakarta City in March 2021. This research is a causal associative study with a cross sectional study design. Population is all in building blood donors at the BDU of Indonesian Red Cross Surakarta city. The sample of this study was 100 respondents with the sampling technique using simple random sampling. The data collection method uses primary data. The data collection tool used a closed questionnaire which was held in March 2021. Simple linear regression analysis is presented in the form of a percentage using the help of IBM SPSS version 26. The significance value is 0.00 <0.05, so it is significant. Analysis of the data using simple linear regression analysis calculation results are 52.1%, meaning that there is an effect of variable X on variable Y and the remaining 47.9% is influenced by other factors. The simple regression coefficient value is 0.411, meaning that the value shows a positive number, so that the direction of the relationship between variables is unidirectional. It can be concluded that there is an influence of blood donor facilities on donor interest in BDU of Indonesian Red Cross Surakarta City.